Guilt emotion and decision-making under uncertainty - Gangemi, Amelia; Rizzotto, Chiara; Riggio, Febronia; Dahò, Margherita; Mancini, Francesco (Frontiers in Psychology, 2025)
This paper examines the impact of moral emotions, such as guilt, on decisions under risk. In two experiments, we demonstrated that guilt emotion influences preferences for risky and riskless choices, depending on the subject’s moral goal, i.e., reparation or expiation, whereas anger consistently elicits a preference for taking risks. Unlike other moral emotions (e.g., anger), guilt is thus not characterized by a fixed preference for either risky or riskless choices. Preferences vary as a function of the option that may satisfy the moral goal, instead of by a form of bias that the different emotions play toward decisions under risk. Finally, in both experiments, responses appear to be based on the framing of the decision problem according to the induced emotional state (guilt or anger), rather than on the descriptions of the outcomes as given in the options (gain-loss framing effect).